The significance of the forensic clinical examination on the judicial assessment of rape complaints – developments and trends. (April 2019) - Kjærulff, Mette Louise B.G.; Bonde, Ulla; Astrup, Birgitte Schmidt
Highlights: The Prosecution Service found a forensic exam of the victim important for the legal process in 49% of cases of sexual assault. A forensic examination of the perpetrator is associated with laying of charges and a guilty verdict. The prosecution was more often aided by the forensic exam in cases of 'conflicting explanations', uncooperative victim or perpetrator denial. The prosecution services' use of a forensic exam of victim and perpetrator has been more frequent in recent years. Abstract: Objective: The aim of this study was to investigate the role of the forensic clinical examination in the judicial assessment made by the Prosecution Service in cases of rape. Methods: All cases of police-reported sexual assault in the county of Funen, Denmark in a six-year period were reviewed, and the retrospective data was collected. Cases in which a forensic clinical examination was performed were included. Results: The Prosecution Service in the county of Funen received 348 police-reported rape cases and of these 184 cases were included. The Prosecution Service stated that the forensic clinical examination (FCE) was important for the decision-making process in approximately half of the cases. The Prosecution Service finding an FCE important due to the presence of relevant findings was significantly associated with the case going to trial, whereas importance due to absence of relevant findings was significantly associated with the cases not going to trial. The only single factor associated with a case going to court and a guilty verdict was an FCE of the alleged perpetrator. There were no crude associations between any other factors i.e. the type of assault, victim injuries or alcohol consumption. In a logistic regression model, however, it was significantly more likely ( p  < 0.05) that a forensic clinical examination of the victim was used in the Prosecution Service's decision if there were both anogenital and extra-genital injuries documented, that could originate from the alleged crime. The odds were 7.83 times higher compared to if no injuries were detected. The Prosecution Service's use of the clinical examination in their argumentation of the decision of a rape complaint has been significantly increasing from 2003 to 2015. Conclusion: The results of the first in-depth analysis of the overall importance of a forensic clinical examination in cases of rape and sexual assault shows that we need to continuously focus on the documentation of sexual assault, as documentation is part of the decision-making process at all stages of the judicial process.